Basic Science in Movement Disorders: Fueling the Engine of Translation into Clinical Practice - Outeiro, Tiago F. (2024)
Basic Science is crucial for the advancement of clinical care for Movement Disorders. Here, we provide brief updates on how basic science is important for understanding disease mechanisms, disease prevention, disease diagnosis, development of novel therapies and to establish the basis for personalized medicine. We conclude the viewpoint by a call to action to further improve interactions between clinician and basic scientists.